2011
DOI: 10.1097/mao.0b013e3182255933
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Versus Intravenous Delivery of Dexamethasone and Dexamethasone Sodium Phosphate to Cochlear Perilymph

Abstract: Administration of dexamethasone IT results in much higher perilymph concentrations and much lower plasma concentrations compared with IV administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 9 publications
3
95
0
2
Order By: Relevance
“…This pattern seems to suggest a lasting benefit -if the treatment effect was to wear off, it would do so more quickly than only after 3 months as small molecules such as the active substance of AM-101 tend to get cleared from the cochlea within a few days already [e.g. Chen et al, 2003;Salt, 2005;Bird et al, 2011]. The gradual improvement is most likely the result of adaptation processes within the auditory system [van de Heyning et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern seems to suggest a lasting benefit -if the treatment effect was to wear off, it would do so more quickly than only after 3 months as small molecules such as the active substance of AM-101 tend to get cleared from the cochlea within a few days already [e.g. Chen et al, 2003;Salt, 2005;Bird et al, 2011]. The gradual improvement is most likely the result of adaptation processes within the auditory system [van de Heyning et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a recently published prospective randomized clinical trial in patients suffering from sudden sensorineural hearing loss [Rauch et al, 2011], which demonstrated comparable therapeutic benefits between a 19-day course of orally administered prednisolone and a regimen of 4 intratympanic injections of methylprednisolone. However, it has been recognized that the systemic route to treat otic disorders is inadequate owing to poor inner ear absorption and significant risks of adverse effects [Bird et al, 2007[Bird et al, , 2011Rauch et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous pharmacokinetic studies of locally-applied corticosteroids in animals (Nomura 1984;Parnes et al 1999;Chandrasekhar et al 2000;Bachmann et al 2001;Hahn et al 2006Hahn et al , 2012Liu et al 2006;Plontke et al 2008b;Yang et al 2008;Wang et al 2009;Borden et al 2011;Salt et al 2011a) and humans (Bird et al 2007;Bird et al 2011), but only a subset of these studies has been analyzed quantitatively to derive an elimination rate. Plontke and analyzed prednisoline data of Bachmann et al (2001) from guinea pigs and found it to be consistent with an elimination half-time from perilymph of 130 min.…”
Section: Introductionmentioning
confidence: 99%